(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
A kinematic assessment is providing information on the relationship of parts of the body to each other. This is useful in measuring joint angles during complex movement and has provided the basis of understanding functional activities comes from kinematic assessments. Purpose: The purpose of this study was to find out the relationship of selected angular & linear kinematic variables with the performance of forward salto technique on floor exercise in artistic gymnastics. Method/Procedure: In the Present study total thirty four male gymnasts (19 to 25 years of age) who had participated in the international and senior national gymnastics tournament were selected as subjects for this study. Purposive sampling technique was used for choosing highly skilled gymnast. Forward salto technique was divided into three phases such as takeoff phase, flight phase and landing phase. The kinematic variables were consisted of selected angular & linear kinematic variables. For the kinematic analysis High speed videography technique was employed. The data were recorded from both planes i.e. sagittal plane and frontal plane. Each subject was given five trials and the best trial was used for analysis. The silicon coach pro 7 and kinovea software were used for analyzing the data. Segmentation method was employed in order to assess to the center of gravity. The relationship of selected angular & linear kinematic variables with the performance of forward somersault on floor exercise in artistic gymnastics was obtained by employing the Spearman Rank Correlation method and the alpha level was set at 0.05 level of significance. Results & Conclusion: The findings of the Spearman rank correlation shows significant relationship between the angle at Left hip joint & Right hip joint at the time of take off phase, negative significant relationship of forward salto performance with hip joint left, hip joint right, and shoulder joint left, elbow joint left and right at the time of flight phase respectively, at the time of Landing phase shows that there exists a significant relationship between forward salto performance and Knee (left), knee joint (Right), hip joint (left) & hip joint (right) as the values were found higher than the tabulated value at .05 level of significance, linear kinematic variable clearly indicates that there exists a significant relationship between Forward salto performance and Total flight duration, Maximum height, Center of gravity at flight time, were found higher than the tabulated value at .05 level of significance. Whereas other selected angular & linear kinematic variables does not show any significant relationship with at the Takeoff Phase, Flight Phase & landing phase because the calculated value was found less than the table value at 0.05 level of significance.